The content of the integrative approach and its role in the formation of creative thinking in students - Ergasheva Fayoza Bahodir qizi, (International Journal of Pedagogics, 2025)
This article explores how an integrative pedagogical approach—one that links multiple subjects, methods, and learning activities—enhances creative thinking among students. Drawing on a mixed-method research design, the study compares traditional single-subject instruction with integrative teaching in two cohorts: high school (Grades 9–11) and undergraduate (first- and second-year) students. Literature and Visual Arts were combined in one group, and Mathematics and Computer Science in another, while control groups followed standard curricula. Over three months, quantitative evaluations (pre- and post-tests) and qualitative insights (observations, interviews, and reflective surveys) were collected to measure changes in creative thinking skills—originality, fluency, and flexibility. Findings indicate that students engaged in integrative tasks performed better on creative assessments, exhibited higher motivation, and demonstrated deeper conceptual understanding. In Literature and Visual Arts, learners developed more evocative writing and artistic interpretations. In Mathematics and Computer Science, they devised innovative solutions, translating abstract concepts into practical computational tasks. The results suggest that integrative pedagogy fosters interdisciplinary connections, stimulating creative cognition and promoting a more holistic educational experience. However, challenges such as curriculum alignment, teacher preparedness, and appropriate assessment methods need to be addressed to fully realize the approach’s benefits.